Circadian Dependence of the Acute Immune Response to Myocardial Infarction - Kilgallen, Aoife B.; van den Akker, Frederieke; Feyen, Dries A. M.; Crnko, Sandra; Snijders Blok, Christian J. B.; Gremmels, Hendrik; du Pré, Bastiaan C.; Reijers, Robin; Doevendans, Pieter A.; de Jager, Saskia C. A.; Sluijter, Joost P. G.; Sampaio-Pinto, Vasco; et al. (Frontiers in Pharmacology, 2022)
Circadian rhythms influence the recruitment of immune cells and the onset of inflammation, which is pivotal in the response to ischemic cardiac injury after a myocardial infarction (MI). The hyperacute immune response that occurs within the first few hours after a MI has not yet been elucidated. Therefore, we characterized the immune response and myocardial damage three hours after a MI occurs over a full twenty-four-hour period to investigate the role of the circadian rhythms in this response. MI was induced at Zeitgeber Time (ZT) 2, 8, 14 and 20 by permanent ligation of the left anterior descending coronary artery. Three hours after surgery, animals were terminated and blood and hearts collected to assess the immunological status and cardiac damage. Blood leukocyte numbers varied throughout the day, peaking during the rest-phase (ZT2 and 8). Extravasation of leukocytes was more pronounced during the active-phase (ZT14 and 20) and was associated with greater chemokine release in blood and expression of adhesion molecules in the heart. Damage to the heart, measured by Troponin-I plasma levels, was elevated during this time frame. Clock gene oscillations remained intact in both MI-induced and sham-operated mice hearts, which could explain the circadian influence of the hyperacute inflammatory response after a MI. These findings are in line with the clinical observation that patients who experience a MI early in the morning (i.e. early active phase) have worse clinical outcomes. This study provides further insight on the immune response occurring shortly after an MI, which may contribute to the development of novel and optimization of current therapeutic approaches.